Increasing Student Learning Motivation Using Keroppi Pouch Learning Media in Social Sciences Subjects for Class V at SDN 024 North Samarinda: Peningkatan Motivasi Belajar Siswa Dengan Menggunakan Media Pembelajaran Kantong Keroppi Pada Mata Pelajaran IPS kelas V SDN 024 samarinda utara - Nur Agus Salim; Euis Kusumarini; Karunia Lestari (Borneo Educational Journal (Borju), 2020)
The researcher conducted a classroom action research to improve students’ learning motivation by using Keroppi pouch as the media of learning. Forty students of class V A at SD Negeri 024 Samarinda Utara were involved as research subjects. The research was conducted in SD Negeri 024 Samarinda Utara as the research setting. At the first cycle, students’ average score was 65.62 with 47.5% students achieved the passing grade. Therefore, the cycle must be continued to the second cycle. At the second cycle, students’ average score was 83.5 with 90% students reached the passing grade. In brief, it can be concluded that the implementation of Keroppi pouch has been effective to improve students’ learning motivation, especially for social science in class V A, since students managed to achieve the passing grade with very good category.